2020
DOI: 10.3311/ppci.15515
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Reinforced Concrete Sheet Pile Wall Element

Abstract: In the forthcoming years intensive renovation and reconstruction works can be expected on the banks’ freshwaters of Hungary. For the rehabilitation of the shores of Lake Velence works are starting in 2020. To support these investments there has been a demand for prefabricated reinforced concrete sheet pile walls. Realizing the opportunity, a major player in the market of pre-fabricated reinforced concrete elements for water way construction, CSOMIÉP Ltd. decided to develop a reinforced concrete sheet pile wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Nearly 20 years of practice in the Qiantang River have shown that the sheet pile groyne system can protect riverbanks and seawalls well, avoiding bucking failures and providing a much longer service period with fewer maintenance costs than traditional groynes [6]. Researchers in Hungary have developed prefabricated concrete sheet pile walls, mainly to prevent erosion and provide places for sports activities along the riverbanks, and used them in the rehabilitation of the shores of Lake Velence in 2020 [15]. Various shapes of sheet piles have also been developed for river management applications.…”
Section: Principles Classification and Characteristics Of Concrete Pilesmentioning
confidence: 99%
“…Nearly 20 years of practice in the Qiantang River have shown that the sheet pile groyne system can protect riverbanks and seawalls well, avoiding bucking failures and providing a much longer service period with fewer maintenance costs than traditional groynes [6]. Researchers in Hungary have developed prefabricated concrete sheet pile walls, mainly to prevent erosion and provide places for sports activities along the riverbanks, and used them in the rehabilitation of the shores of Lake Velence in 2020 [15]. Various shapes of sheet piles have also been developed for river management applications.…”
Section: Principles Classification and Characteristics Of Concrete Pilesmentioning
confidence: 99%
“…The anti-sliding pile system is the most conventional method to reinforce the slope. According to different landslide geological conditions, landslide scales and project requirements, the anti-sliding pile system can be divided into common anti-sliding pile (CASP), anchored anti-sliding pile (AASP) and combined pile (CP) [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%